Quantification of oxide particle composition in model oxide dispersion strengthened steel alloys - London, A; Lozano-Perez, S; Moody, M; Amirthapandian, S; Panigrahi, B; Sundar, C; Grovenor, C (Elsevier, 2015)
Oxide dispersion strengthened ferritic steels (ODS) are being considered for structural components of future designs of fission and fusion reactors because of their impressive high-temperature mechanical properties and resistance to radiation damage, both of which arise from the nanoscale oxide particles they contain. Because of the critical importance of these nanoscale phases, significant research activity has been dedicated to analysing their precise size, shape and composition (Odette et al., Annu. Rev. Mater. Res. 38 (2008) 471-503 [1]; Miller et al., Mater. Sci. Technol. 29(10) (2013) 1174-1178 [2]). As part of a project to develop new fuel cladding alloys in India, model ODS alloys have been produced with the compositions, Fe-0.3Y2O3, Fe-0.2Ti-0.3Y2O3 and Fe-14Cr-0.2Ti-0.3Y2O3. The oxide particles in these three model alloys have been studied by APT in their as-received state and following ion irradiation (as a proxy for neutron irradiation) at various temperatures. In order to adequately quantify the composition of the oxide clusters, several difficulties must be managed, including issues relating to the chemical identification (ranging and variable peak-overlaps); trajectory aberrations and chemical structure; and particle sizing. This paper presents how these issues can be addressed by the application of bespoke data analysis tools and correlative microscopy. A discussion follows concerning the achievable precision in these measurements, with reference to the fundamental limiting factors.